Transparent P(VDF-HFP) Coatings for Enhancing Fungal Resistance, Hydrophobicity, and Durability of Krajood-Based Natural Fibers - Pethuan, Sirikun; Tammachat, Nattavadee; Kaew-on, Chaiporn; Siri, Ratchanewan; Tohluebaji, Nikruesong; Channuie, Phongpichit; Yuennan, Jureeporn (Trends in Sciences, 2025)
This study investigates the use of poly(vinylidene fluoride-co-hexafluoropropylene) [P(VDF-HFP)] as a transparent, water-repellent, and antifungal coating for Krajood (Lepironia articulata) products—traditional natural fibers widely used in Thailand. Coatings with P(VDF-HFP) were formulated at concentrations ranging from 2.5 to 25% and applied via a solution casting technique. The surface, thermal, mechanical, and biological properties of the coated samples were systematically characterized and compared to uncoated and lacquer-coated controls using Fourier-transform infrared spectroscopy (FTIR), water contact angle (WCA) measurements, thermogravimetric analysis (TGA), scanning electron microscopy (SEM), and tensile testing. Results indicate that the 15% P(VDF-HFP) coating provides the most optimal performance, offering high hydrophobicity (WCA = 124.2°), enhanced tensile strength (112.26 MPa), superior thermal resistance (onset degradation at 241.9 °C), and significant fungal inactivation over a 30-day incubation period. The formation of a microporous surface structure, due to slow solvent evaporation, was found to play a key role in improving both water repellency and fungal resistance. These findings demonstrate the potential of P(VDF-HFP) coatings in extending the lifespan and functionality of natural fiber products, providing a sustainable alternative for moisture-prone applications. HIGHLIGHTS A transparent P(VDF-HFP) coating was developed to improve the water repellency, fungal resistance, and durability of Krajood natural fibers. The optimal performance was achieved at 15% P(VDF-HFP), offering high tensile strength (112.26 MPa), strong hydrophobicity (WCA = 124.2°), and delayed thermal degradation (241.9 °C). Microporous surface morphology formed during drying enhanced both hydrophobic and antifungal properties through the Cassie–Baxter mechanism. Compared to lacquer, P(VDF-HFP) provided superior mechanical, thermal, and biological resistance without altering the fiber’s natural aesthetics. GRAPHICAL ABSTRACT